Damage caused by Wegener's granulomatosis and its treatment: prospective data from the Wegener's Granulomatosis Etanercept Trial (WGET). - Seo, P; Min, Y; Holbrook, J; Hoffman, G; Merkel, P; Spiera, R; Davis, J; Ytterberg, SR; St Clair, E; McCune, W; Specks, U; Allen, N; et al. (2005)
OBJECTIVE: To analyze damage occurring in patients with Wegener's granulomatosis (WG) enrolled in the WG Etanercept Trial (WGET) and to correlate that damage with disease activity, adverse events, and quality of life. METHODS: The Vasculitis Damage Index (VDI) was applied to all 180 patients at trial entry and every 6 months throughout the trial. Items of damage were analyzed by presumed etiology (i.e., secondary to WG, to therapy, or both) and time of occurrence. Spearman's rank correlation coefficients were calculated between VDI scores and the Birmingham Vasculitis Activity Score for WG (BVAS/WG), frequency of flares, number of adverse events, and the patients' quality-of-life assessments. RESULTS: The mean VDI score was 1.3 at the study enrollment and 1.8 at the end of the trial. This increase was due to damage that occurred despite (or because of) therapy, including visual impairment, hearing loss, nasal blockade, pulmonary fibrosis, hypertension, renal insufficiency, peripheral neuropathy, gonadal failure, and diabetes mellitus. Only 11% of the enrolled patients had not sustained a single VDI item after 1 year of enrollment. When adjusted for baseline VDI, the baseline BVAS/WG correlated moderately well with the VDI score at 1 year (r = 0.20, P = 0.015). Increases in adjusted VDI scores also correlated with the number of adverse events, particularly among patients with limited WG (P = 0.06). CONCLUSION: Damage from both active disease and its treatment remain important problems for patients with WG. Despite the dramatic improvements in patient survival achieved over the last several decades, only a few patients with WG emerge from a period of active disease without sustaining some damage from the disease itself, its treatment, or both. An important measure of future therapeutic approaches will be their ability to reduce the damage accrued over time.